Biophysically Based Modeling of the Interstitial Cells of Cajal: Current Status and Future Perspectives - Lees-Green, Rachel; Du, Peng; O'Grady, Greg; Beyder, Arthur; Farrugia, Gianrico; Pullan, Andrew (Frontiers in Physiology, 2011)
Gastrointestinal motility research is progressing rapidly, leading to significant advances in the last 15 years in understanding the cellular mechanisms underlying motility, following the discovery of the central role played by the interstitial cells of Cajal (ICC). As experimental knowledge of ICC physiology has expanded, biophysically-based modelling has become a valuable tool for integrating experimental data, for testing hypotheses on ICC pacemaker mechanisms, and for applications in in silico studies including in multiscale models. This review is focused on the cellular electrophysiology of ICC. Recent evidence from both experimental and modelling domains have called aspects of the existing pacemaker theories into question. Therefore, current experimental knowledge of ICC pacemaker mechanisms is examined in depth, and current theories of ICC pacemaking are evaluated and further developed. Existing biophysically-based ICC models and their physiological foundations are then critiqued in light of the recent advances in experimental knowledge, and opportunities to improve these models are identified. The review concludes by examining several potential clinical applications of biophysically-based ICC modelling from the subcellular through to the organ level, including ion channelopathies and ICC network degradation.